FROM DIGITAL PLATFORMS TO LEARNING QUALITY: A MANAGEMENT MODEL OF LEARNING INFORMATION SYSTEMS IN SECONDARY EDUCATION - Aman Subakti; Deny Hadi Siswanto; Kintoko Kintoko (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the management model of the learning information system in improving the quality of learning at SMA Muhammadiyah Mlati. This study employed a qualitative approach with a descriptive research design. The participants consisted of the principal, the vice-principal for curriculum, teachers, and students who were involved in the use of the learning information system. Data were collected through in-depth interviews, classroom observations, and documentation analysis of school records, including schoolwork programs, digital-based lesson plans, and reports on the use of learning platforms. The collected data were analyzed using qualitative data analysis techniques involving data reduction, data display, and conclusion drawing. The findings indicate that the management of the learning information system is implemented through systematic stages of planning, implementation, monitoring, and evaluation. The implementation of the system supports the organization of learning materials, assignments, and assessments more effectively while facilitating communication between teachers and students. In addition, the system increases student engagement and participation in learning activities. Therefore, the management of the learning information system contributes positively to improving the quality of learning.